2022
DOI: 10.1093/ije/dyac145
|View full text |Cite
|
Sign up to set email alerts
|

Mortality among twin individuals exposed to loss of a co-twin

Abstract: Background Although the death of a child, sibling or spouse has been associated with elevated risk of mortality, less is known about the survival of twin siblings exposed to a co-twin loss. Methods In a Swedish population-based sibling-matched cohort, we compared the mortality of 5548 twin individuals who lost their co-twin between 1932 and 2011 with that of 27 740 age-matched and sex-matched twin individuals without such a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…Considering different causes of sibling death, we found that individuals experiencing sibling loss due to CVD had a higher CVD risk, which supports the hypothesis that common genetic and environmental cardiovascular risk factors that clustered in families are likely to be an important explanation for the association between bereavement and CVD . Nevertheless, we also observed an increased risk of CVD if the sibling died of a non-CVD cause, which suggests an independent role of stress-related mechanisms between sibling death and CVD incidence .…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Considering different causes of sibling death, we found that individuals experiencing sibling loss due to CVD had a higher CVD risk, which supports the hypothesis that common genetic and environmental cardiovascular risk factors that clustered in families are likely to be an important explanation for the association between bereavement and CVD . Nevertheless, we also observed an increased risk of CVD if the sibling died of a non-CVD cause, which suggests an independent role of stress-related mechanisms between sibling death and CVD incidence .…”
Section: Discussionsupporting
confidence: 82%
“…[9][10][11][12][29][30][31] Nevertheless, we also observed an increased risk of CVD if the sibling died of a non-CVD cause, which suggests an independent role of stress-related mechanisms between sibling death and CVD incidence. [9][10][11][12][29][30][31] Psychological stress following bereavement could activate acute stress responses, which may lead to changes in brain stress-responsive neurocircuitry and then stimulate peripheral physiological responses, including the autonomic nervous system response, hypothalamic-pituitary-adrenal responses, and sterile inflammation. [38][39][40] These stress responses would lead to pathophysiological…”
Section: Jama Network Open | Cardiologymentioning
confidence: 49%
See 3 more Smart Citations